Alternative monolithic/composite carbons for adsorption generators and simulation for optimal performance. (5th November 2017) - Rivero-Pacho, Angeles M.; Critoph, Robert E.; Metcalf, Steven J.
Abstract: This paper presents the development and thermal properties study of three types of carbon composites with enhanced thermal properties along with the optimisation of the geometry of the shell and tube generators currently used at the University of Warwick for the development of carbon-ammonia heat pumps. The three carbon composites developed use lignin binder, silanes binder and Expanded Natural Graphite (ENG) as a way of enhancing their thermal properties in order to perform more efficiently in a refrigeration or heating system. Two techniques were used in order to obtain the thermal properties: Anter and HyperFlash thermal conductivity instruments. Results show that ENG increases drastically the thermal conductivity of the samples (up to 3.4 W/(mK)) but reduces the carbon density (450 kg/m 3 ) and increases the thermal mass of the system. Lignin binder samples show lower thermal conductivities (0.3 W/(mK)) but higher carbon densities (750 kg/m 3 ) which increases the performance of the machine. Thermal conductivities of samples were also obtained for a wide range of working temperatures (25–200 °C). The current development of gas fired heat pumps at Warwick uses shell and tube adsorption generators with over 1000 water tubes of 1.2 mm diameter on a 3 mm pitch. This geometry is not optimised and a dynamic simulation program has been written to determine how far from optimal the design is and also whether alternative designs offer advantages. The results presented show that the shell and tube is close to optimal for its type but that finned tube designs might offer improvements.